Management of Pediatric Psoriasis: A U.S. Survey Based on Visits from the National Ambulatory Medical Care Survey (NAMCS) - Rachel E. Tao; Jessica N. Pixley; Phillip G. Holovach; Alan B. Fleischer; Steven R. Feldman (Adis, Springer Healthcare, 2023)
Abstract Introduction Approximately one-third of psoriasis cases present in the first two decades of life. Many psoriasis treatments are approved by the U.S. Food and Drug Administration (FDA) for adults, including topical agents, systemic non-biologic agents, and systemic biologic agents. Only a handful of psoriasis treatments are FDA approved for children. Given the constantly evolving landscape of pediatric psoriasis management, our aim is to characterize how children with psoriasis are treated in the U.S. Methods Data from the 2003-2016 and 2018 National Ambulatory Medical Care Survey (NAMCS) were used to evaluate patient demographics and treatment patterns for visits of children with psoriasis. Visits were stratified by those with a diagnosis of psoriasis and those for children with a diagnosis of psoriasis. Separate analyses for visits of children with a diagnosis of psoriasis were performed, including for sex, race, ethnicity, age, specialty of provider seen, and medications prescribed. Results Pediatric psoriasis visits accounted for 3.3% of visits with psoriasis from 2003 to 2016 and in 2018; about one-third of those visits were to primary care providers. Children with psoriasis were prescribed a variety of topical and systemic medications, of which the most frequently prescribed treatments were topical tacrolimus, followed by topical clobetasol and topical betamethasone dipropionate or betamethasone valerate. Etanercept was the only biologic prescribed to children. At least 59% of the visits for children with a diagnosis of psoriasis included a topical prescription while at least 5.3% of the visits included a systemic prescription. Conclusion Use of off-label treatments was common for pediatric psoriasis. Most children with psoriasis were treated with topicals, of which tacrolimus, an unapproved treatment, was the most common. The frequent use of tacrolimus could indicate an avoidance of corticosteroids in children.